NEWS PORTAL OF DAILY LAMPUNG NEWSPAPER BASED ON ANDROID - saptomi, erland gili; Yusman, Machudor; Febriansyah, Febi Eka (Universitas Lampung, 2016)
Technology developments have a positive impact in delivery of news or information to the public to be more easily and quickly without any distance limitation in access news. This is supported by the development of internet access which increase rapidly, so that everyone in the world can access or share information in real time (without any lag time). News Portal Of Daily Lampung Newspaper Based On Android is an application that provides convenience to the public in obtaining information or news. News Portal Based On Android provide news which taken from website lampungnewspaper.citm.co.id. Things become a study in this thesis is connecting between Android platform with website database platform using library Volley. News Portal is made using Android Studio and retrieve data from database website lampungnewspaper.citm.co.id with Waterfall method.